Pengaruh Pelatihan Dan Budaya Kerja Terhadap Kinerja Pengrajin Batik Tulis Desa Paseseh Kecamatan Tanjung Bumi - Rumzah, Rumzah; Kuswinarno, Mudji (Eco-Entrepreneur, 2023)
This research was conducted to batik craftsmen in Paseseh Village, Tanjung Bumi District. Human resource plays an essential role as the main basis of a business in gaining competitive advantages. One of the small businesses occupied by the community is hand-drawn batik which still applied the traditional production process. Efforts to increase public interest in creating optimal products require craftsmen with good performance. This study aims to reach the following goals: to determine the effect of training on the performance of batik craftsmen, to determine the effect of work culture on the performance of hand-drawn batik craftsmen, and to determine the effect of training and work culture on the performance of hand-drawn batik craftsmen in Paseseh Village, Tanjung Bumi, District, as well as to find out which training and work culture have the dominant influence on the performance of batik craftsmen in Paseseh Village, Tanjung Bumi District. The method used in this research was quantitative with a total population of 90 craftsmen, thus, this research is categorized as population research. The data collection procedures involved interviews, questionnaires, and a literature study. The analysis techniques used were the Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Linear Regression Test, and Hypothesis Test. The results of this study indicate that 1) Training has a positive and significant effect on the performance of craftsmen with a t-count of 4.986 t-table of 1.66235, with a significant level of 0.000 0.05, and with a β value of 0.378. 2) Work culture has a positive and significant effect on the performance of craftsmen with a t-count of 4.467 t-table of 1.66235, with a significant level of 0.000 0.05, and with a β value of 0.377. 3) Training and work culture have a positive and significant effect on the performance of craftsmen with an F-count of 113.560 F-table of 3.10 and with a significant level of 0.000 0.05. Dominant training affects the performance of craftsmen with a Beta value of 0.472